The complex binding mode of the peptide hormone H2 relaxin to its receptor RXFP1 - Sethi, Ashish (Nat Commun, 2016)
H2 relaxin activates the relaxin family peptide receptor-1 (RXFP1), a class A G-protein coupled receptor, by a poorly understood mechanism. The ectodomain of RXFP1 comprises an N-terminal LDLa module, essential for activation, tethered to a leucine-rich repeat (LRR) domain by a 32-residue linker. H2 relaxin is hypothesized to bind with high affinity to the LRR domain enabling the LDLa module to bind and activate the transmembrane domain of RXFP1. Here we define a relaxin-binding site on the LDLa-LRR linker, essential for the high affinity of H2 relaxin for the ectodomain of RXFP1, and show that residues within the LDLa-LRR linker are critical for receptor activation. We propose H2 relaxin binds and stabilizes a helical conformation of the LDLa-LRR linker that positions residues of both the linker and the LDLa module to bind the transmembrane domain and activate RXFP1.